Taxonomic revaluation of the Polylepis pauta and P. sericea (Rosaceae) from Ecuador - Espinoza T.E.B. (2020)
We conducted a taxonomic revaluation of the Polylepis pauta and P. sericea complexes in Ecuador, recognizing five species, three of which are described as new: Polylepis humboldtii sp. nov., P. loxensis sp. nov., P. longipilosa sp. nov., P. ochreata, and P. pauta. We provide descriptions of all species, full specimen citations, and updated keys to genus Polylepis in Ecuador and to the P. pauta and P. sericea complexes in general. Copyright © 2020 Magnolia Press